2019
DOI: 10.1002/jsfa.9611
|View full text |Cite
|
Sign up to set email alerts
|

Structural, antioxidant and adsorption properties of dietary fiber from foxtail millet (Setaria italica) bran

Abstract: BACKGROUND Foxtail millet (Setaria italica) bran is a by‐product of millet processing, rich in dietary fiber (DF) and has great application value. A comparative study was conducted to explore the differences in structural and functional properties among millet bran DF, soluble dietary fiber (SDF) and insoluble dietary fiber (IDF). RESULTS There was a significant difference in the content of monosaccharides between SDF and IDF, in which xylose, arabinose and glucose were the main compositions. The results of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…Nevertheless, different surface characteristics were demonstrated in the SDF (Figure 1c), with small irregular blocking structures. These results were similar to previously reported foxtail millet bran DF (Dong et al, 2019;Zhu et al, 2018).…”
Section: Scanning Electron Microscopysupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, different surface characteristics were demonstrated in the SDF (Figure 1c), with small irregular blocking structures. These results were similar to previously reported foxtail millet bran DF (Dong et al, 2019;Zhu et al, 2018).…”
Section: Scanning Electron Microscopysupporting
confidence: 93%
“…All dietary fiber samples from potato residues showed α-AAIR, SDF (17.89%) and TDF (11.40%) gave the higher α-AAIR followed by IDF (3.86%) (Table 2). Similar observation found in TDF (14.02%), TA B L E 2 Functional properties of total, insoluble, and soluble dietary fiber obtained from potato residues IDF (2.89%), and SDF (17.92%) from foxtail millet (Dong et al, 2019).…”
Section: α-Amylase Activity Inhibition Ratiosupporting
confidence: 76%
“…In addition, ascorbic acid and tocopherol are also important non-enzymatic antioxidants that can regulate the levels of ROS [22]. Recent studies have found that many compounds derived from the dietary fibers can scavenge ROS [23,24]. Moreover, the antioxidant effect is a key biological effect derived from many plant-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being a daily nutritional source, small millets, including foxtail millet, have anti-inflammatory properties and can therefore be used for the prevention of related chronic diseases, such as atherosclerosis and diabetes ( 20 , 21 ). Along with its superior nutritional properties and documented anti-inflammatory function, foxtail millet is also rich in non-nutrient prebiotics, such as polyphenols and dietary fibers ( 22 ), suggesting its possible positive effects on the gut microbiota and IBD. Bond polyphenols and peroxidase of foxtail millet bran have also been reported to inhibit colitis-induced carcinogenesis in a mouse model ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%